Disaggregating polyploidy, parental genome dosage and hybridity contributions to heterosis in Arabidopsis thaliana. Issue 2 (23rd September 2015) - Fort, Antoine; Ryder, Peter; McKeown, Peter C.; Wijnen, Cris; Aarts, Mark G.; Sulpice, Ronan; Spillane, Charles
Summary: Heterosis is the phenomenon whereby hybrid offspring of genetically divergent parents display superior characteristics compared with their parents. Although hybridity and polyploidy can influence heterosis in hybrid plants, the differential contributions of hybridity vs polyploidy to heterosis effects remain unknown. To address this question, we investigated heterosis effects on rosette size and growth rate of 88 distinct F1 lines of Arabidopsis thaliana consisting of diploids, reciprocal triploids and tetraploids in isogenic and hybrid genetic contexts. 'Heterosis without hybridity' effects on plant size can be generated in genetically isogenic F1 triploid plants. Paternal genome excess F1 triploids display positive heterosis, whereas maternal genome excess F1 s display negative heterosis effects. Paternal genome dosage increases plant size in F1 hybrid triploid plants by, on average, 57% (in contrast with 35% increase displayed by F1 diploid hybrids). Such effects probably derive from differential seed size, as the growth rate of triploids was similar to diploids. Tetraploid plants display a lower growth rate compared with other ploidies, whereas hybrids display increased early stage growth rate. By disaggregating heterosis effects caused by hybridity vs genome dosage, we advance our understanding of heterosis in plants and facilitate novel paternal genome dosage‐based strategies to enhance heterosis effects in crop plants.